Analysis of Inequality Structure and Its Correlation With Government Expenditure : A Study of Western Indonesia - Ririn Nopiah; Barika Barika; Septriani Septriani (International Journal of Economics, Management and Accounting, 2024)
Efforts to reduce regional inequality are aimed at Accelerate equitable development . Implementing a healthy fiscal policy through government spending is a form of effort to reduce this inequality . Government spending can provide intervention in regional policies to boost the economy through regional government spending and revenue . This study examines the development of inter -regional inequality mapping through the Class typology method , measuring inequality with the Williamson index , and testing multiple linear regression to analyze regional government spending on inequality in the Western Region of Indonesia in 2019-2022. The results show that the average regional inequality index is at moderate inequality , namely 0.465. In addition , the regression results show that efforts to reduce regional inequality aimed at Accelerate equitable development through fiscal policy trend to be ineffective . The contribution of government spending has not been significant impact on reduce inequality . Therefore , evaluation and improvement in government spending policies are needed so that they can be more effective in achieving the goal of alleviating regional inequality in the western region of Indonesia.